Current Benefits of Wildfire Smoke for Yields in the US Midwest May Dissipate by 2050 - Behrer, Arnold Patrick; Wang, Sherrie (Washington, DC: World Bank, 2022)
Wildfires throughout western North America produce smoke plumes that can stretch across the agricultural regions of the American Midwest. Climate change is likely to increase the number and size of these fires and subsequent smoke plumes. These smoke plumes change direct, diffuse, and total sunlight during the crop growing season and consequently influence yields of both corn and soybeans. The analysis in this paper uses a twelve-year panel of county-level yields from all counties east of the 100th meridian combined with measures of exposure to smoke plumes of low and high density during the growing season. It shows that low-density plumes enhance yields, likely by increasing in the fraction of diffuse light, while high-density plumes decrease yields. Because there are more low-density plumes today, the net effect is a slight increase in yields on average. As climate change makes wildfires larger and more frequent, the overall impact of smoke on yields is expected to be substantially more negative.